Surgical repair of parastomal bulging: a retrospective register‐based study on prospectively collected data. (12th July 2020) - Krogsgaard, M.; Gögenur, I.; Helgstrand, F.; Andersen, R. M.; Danielsen, A. K.; Vinther, A.; Klausen, T. W.; Hillingsø, J.; Christensen, B. M.; Thomsen, T.
Abstract: Aim: The aim of this work was to examine (1) the incidence of primary repair, (2) the incidence of recurrent repair and (3) the types of repair performed in patients with parastomal bulging. Method: Prospectively collected data on parastomal bulging from the Danish Stoma Database were linked to surgical data on repair of parastomal bulging from the Danish National Patient Register. Survival statistics provided cumulative incidences and time until primary and recurrent repair. Results: In the study sample of 1016 patients with a permanent stoma and a parastomal bulge, 180 (18%) underwent surgical repair. The cumulative incidence of a primary repair was 9% [95% CI (8%; 11%)] within 1 year and 19% [95% CI (17%; 22%)] within 5 years after the occurrence of a parastomal bulge. We found a similar probability of undergoing primary repair in patients with ileostomy and colostomy. For recurrent repair, the 5‐year cumulative incidence was 5% [95% CI (3%; 7%)]. In patients undergoing repair, the probability was 33% [95% CI (21%; 46%)] of having a recurrence requiring repair within 5 years. The main primary repair was open or laparoscopic repair with mesh (43%) followed by stoma revision (39%). Stoma revision and repair with mesh could precede or follow one another as primary and recurrent repair. Stoma reversal was performed in 17% of patients. Conclusion: Five years after the occurrence of a parastomal bulge the estimated probability of undergoing a repair was 19%. Having undergone a primary repair, the probability of recurrent repair was high. Stoma reversal was more common than expected.